Digital applications in implementation of smart grid - Islam, Syed (IEEE, 2017)
A smart grid is an electricity transmission and distribution network that embeds digital and other advanced ICT technologies to sense, monitor, communicate and manage the energy flows, real time electricity asset management, and take online decision from all generation sources to meet the varying electricity demands of end-users. Smart Grids oversees the real time capabilities of the generating, transmitting, distribution assets and allows the power system operators manage the balance between generation and load requirements at most efficient manner. Smart Grid is aimed at maintaining system resiliency, stability, reliability to regulatory standards and at the same time minimises the environmental impact by allowing maximum renewable power generation connected to the grid. The role of modern digital devices and IT technologies are critical to achieve the above objectives. In this paper, some of the digital technology applications in Demand Side Management, Automated Tariff Structure, and Protection of modern substation are presented.